2015
DOI: 10.1016/j.mehy.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants may lead to a decrease in niacin and NAD in patients with poor dietary intake

Abstract: The term niacin is the generic name for the two compounds nicotinic acid and nicotinamide, the major dietary precursors for two important coenzymes, nicotinamide adenine dinucleotide (NAD) and its phosphorylated form, NADP. Niacin is important for the maintenance of cellular integrity and energy production and is involved in more than 500 intracellular reactions. Deficiencies of niacin may contribute to neuropsychiatric and neurodegenerative disorders. Patients who develop nutritional deficiencies as a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…Our finding was in accordance with previous clinical studies which reported that antidepressants are associated with NAD deficiency, especially in patients with inadequate amino acid intake [58]. Thus, it is important to also consider how SSRI, SNRI, and tricyclic antidepressants may affect the NAD level and influence the immune system by regulating immune reactivity [59], altering cytokine responses [60], and inhibiting immune cells and the KP as a result of its anti-inflammatory effects [26,61]. However, we cannot clarify the combined effects from the genetic and pharmacology level; further studies are warranted.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding was in accordance with previous clinical studies which reported that antidepressants are associated with NAD deficiency, especially in patients with inadequate amino acid intake [58]. Thus, it is important to also consider how SSRI, SNRI, and tricyclic antidepressants may affect the NAD level and influence the immune system by regulating immune reactivity [59], altering cytokine responses [60], and inhibiting immune cells and the KP as a result of its anti-inflammatory effects [26,61]. However, we cannot clarify the combined effects from the genetic and pharmacology level; further studies are warranted.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies, including clinical trials and animal models, suggested the link between NAD deficiency and several psychiatric disorders, such as chronic schizophrenia [23], anxiety disorder [24], and bipolar disorder type II [25]. NAD deficiency is also linked to MDD patients treated with antidepressants [26]. However, it seems that there have been limited genetic studies focused on the link between NAD homeostasis and psychiatric disorders, especially MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Fármacos antidepressivos têm efeito anti-inflamatório, incluindo a redução de interferon-gama e, portanto, a inibição de indolamina 2,3-dioxigenase (IDO), a enzima limitante da velocidade da via da quinurenina. Portanto, pacientes com dieta pobre em micronutrientes, tratados com antidepressivos, estão em risco de desenvolver deficiência de niacina NAD com possível desenvolvimento de sintomas neuropsiquiátricos associados (17).…”
Section: Resultsunclassified
“…In a 12-week double-blind study, reduced impulsiveness, hyperactivity, and social difficulties were seen in children supplemented with zinc sulfate (150mg). 30 Deficiencies of zinc and niacin levels have been seen in depressed patients, and hence dietary supplements of zinc and niacin could substantially improve symptoms of depression [52][53][54].…”
Section: Discussionmentioning
confidence: 99%